Gizi Buruk dalam Perspektif Islam: Respon Teologis Terhadap Persoalan Gizi Buruk - Egi Sukma Baihaki (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
AbstractHuman beings are composed of various elements. In life, people can not be separated from the various needs of the body which binds including in terms of food. However, with various types of food that sometimes people do not selectively forget the value of nutrients contained in the food. Nutrition is very important for the human body because with adequate nutrition is able to maintain growth and health. The problem of malnutrition is kept up to haunt the community each year. With the emergence of several cases of malnutrition, this paper seeks to discuss solutions offered by Islam to these problems.